The Influence of Debt to Equity Ratio and Total Asset Turnover on Company Value with Return on Assets as an Intervening Variable - Ningsih, Yulia Lestari; Sutrisno,; Rr. Hawik Ervina Indiworo, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The research aims to test and analyze the effect of debt to equity ratio and total asset turnover on company value with return on assets as an intervening variable in cigarette companies listed on the IDX for the 2019-2023 period. This type of research is quantitative research. The population of this research is cigarette companies registered on the IDX for the 2019-2023 period. The sampling technique uses purposive sampling. The data analysis technique uses structural equation modeling or SEM. Data processing uses smartPLS 3.2.9 software. The results of this research are that the debt to equity ratio, total asset turnover, and return on assets have an effect on company value. Total asset turnover influences return on assets. Meanwhile, the debt to equity ratio has no effect on return on assets. Total asset turnover can influence company value through the mediation of return on assets. Meanwhile, the debt to equity ratio cannot influence company value through the mediation of return on assets.